Impact of health system governance on healthcare quality in low-income and middle-income countries: a scoping review - George, Joby; Jack, Susan; Gauld, Robin; Colbourn, Timothy; Stokes, Tim (BMJ open, 2023)
IntroductionImproving healthcare quality in low-/middle-income countries (LMICs) is a critical step in the pathway to Universal Health Coverage and health-related sustainable development goals. This study aimed to map the available evidence on the impacts of health system governance interventions on the quality of healthcare services in LMICs.MethodsWe conducted a scoping review of the literature. The search strategy used a combination of keywords and phrases relevant to health system governance, quality of healthcare and LMICs. Studies published in English until August 2023, with no start date limitation, were searched on PubMed, Cochrane Library, CINAHL, Web of Science, Scopus, Google Scholar and ProQuest. Additional publications were identified by snowballing. The effects reported by the studies on processes of care and quality impacts were reviewed.ResultsThe findings from 201 primary studies were grouped under (1) leadership, (2) system design, (3) accountability and transparency, (4) financing, (5) private sector partnerships, (6) information and monitoring; (7) participation and engagement and (8) regulation.ConclusionsWe identified a stronger evidence base linking improved quality of care with health financing, private sector partnerships and community participation and engagement strategies. The evidence related to leadership, system design, information and monitoring, and accountability and transparency is limited.